Evaluation of Red Cell Distribution Width to Lymphocyte Ratio as Potential Biomarker for Detection of Colorectal Cancer. (31st July 2019) - Huang, Jiahao; Zhao, Yang; Liao, Lin; Liu, Shun; Lu, Shaolong; Wu, Changtao; Wei, Chuanyi; Xu, Shaoqiang; Zhong, Huage; Liu, Junjie; Guo, Yun; Zhang, Sen; et al.
Abstract : Background and Aim . Colorectal cancer (CRC) is the third most lethal cancer globally. This study sought to determine the feasibility of using red cell distribution width-to-lymphocyte ratio (RLR) as a tool to facilitate CRC detection. Methods . Seventy-eight healthy controls, 162 patients diagnosed with CRC, and 94 patients with colorectal polyps (CP) from June 2017 to October 2018 were retrospectively reviewed. Clinical data were obtained to analyze preoperative RLR level, and receiver operating characteristic (ROC) curve analysis was performed to estimate the potential role of RLR as a CRC biomarker. Results . RLR was higher in patients with CRC than in healthy participants ( P < 0.05). ROC analysis indicated that combined detection of RLR and CEA appears to be a more effective marker to distinguish among controls, CP, and CRC patients, yielding 56% sensitivity and 90% specificity. RLR levels were significantly greater in those who had more advanced TNM stages ( P < 0.05) and patients with distant metastasis stages ( P < 0.05). Conclusions . RLR might serve as a potential biomarker for CRC diagnosis.